Environmental Health in Nicaragua : Study 1 Technical Annexes - World Bank (Washington, DC, 2015)
Globally, an estimated 24 percent of the disease burden (healthy life years lost) and an estimated 23 percent of all deaths (premature mortality) are attributable to environmental risks (World Health Organization, or WHO 2006). The burden of disease is unequally shared, with the children and the poor being particularly affected. Among children between the ages 0 and 14, the proportion of deaths attributable to environmental risks, such as poor water and sanitation, indoor air pollution and vector-borne diseases, is estimated to be as high as 36 percent (WHO 2006). Several key messages have emerged from the process of putting together this study: (i) environmental health risks impose a significant burden on Nicaraguas economy, amounting to 2.6 billion Nicaraguan Cordoba (NIO) or 2.4 percent of the countrys Gross Domestic Product (GDP), and result in premature deaths and infections, especially in children under five; (ii) cost-effective interventions to address these environmental health risks exist and should be prioritized in Nicaragua; (iii) country-specific health and environmental data are somewhat limited, especially in the case of air quality, and data collection and monitoring need to be further strengthened; and (iv) the capacity of Ministry of Environment and Natural Resources (MARENA) and Ministry of Health (MINSA) staff to conduct environmental health costing analysis needs to be strengthened through proper training.